Enhanced Bax upregulating in mitochondria for deep tumor therapy based on SO2 prodrug loaded Au–Ag hollow nanotriangles. (August 2020) - Xu, Min; Lu, Qianglan; Song, Yilin; Yang, Lifang; Li, Jining; Li, Nan
Abstract: Nowadays, limited deep tumor penetration and lower therapeutic effect are still the major obstacle in nanomedicines for cancer therapy. Here, we developed high-efficiency nanocomposites, SO2 prodrug (BTS) loaded Au–Ag hollow nanotriangles (Au–Ag-BTS HTNs), which could not only synergistically upregulate Bax expression in mitochondria, but also be triggered by acidic tumor microenvironment to generate SO2 for deep tumor therapy. Upon NIR laser irradiation, Au–Ag hollow nanotriangles (Au–Ag HTNs) produced plenty of heat for photothermal therapy (PTT), while the acidic condition in tumor cells induced on-demand SO2 release from BTS for deep tumor therapy. More importantly, the combined therapy could simultaneously upregulate the expression of apoptosis factor Bax as well as downregulate Bcl-2 in mitochondria, which would induce an increase of Caspase-3 expression to accelerate the apoptosis of tumor cells, thereby achieving a win-win cooperation. The results indicated that enhanced deep tumor therapeutic effect based on Au–Ag-BTS HTNs was realized in vitro and in vivo. Such pH-triggered SO2 therapy offered a novel strategy for responding tumor microenvironment and improving penetration and heterogeneity distribution of nanotherapeutics in tumor.